Justice in Deuteronomy 16:218-20: A Sine Qua Non for Yahweh’s Covenant Fulfillment - Bello, Olajide Emmanuel (KWASU Journal of Religious Studies, 2019)
The derek wamidhar (exodus and desert) experience of the Israelites was monitored by YHWH and guarded by the sinatic torah waberith (law and covenant). YHYH made laws for his people so that they might know how to relate well with him and wiith one another in a humane and fair manner. Laws are usually enacted to point out sin, make people avoid sinful habits and practices and mere out punishments for culprits so as to maintain orderliness and protect people's rights in the society. Thus- YHWH wanted justice, the fair treatment of people and sagacious ruling in all matters, even those which the written laws may not cover verbatim. This paper therefore seeks to examine the concept of justice in Deuteronomy 16: l8-20 as a prerequisite to enjoying the benefits YHWH had provided for the Israelites in the land of Canaan. Hermeneutical research approach was adopted, to clearly delineat the concepts of justice in the context of Deut 16:18-20. It was discovered that despite the fact that Judges were appointed inequality, oppression, bribery and corruption still persisted among the Israelites, which YHWH pointed out were factors responsible for their untimely death and poverty. The paper concluded by recommending that credibility should not be compromised in appointing Judges; the judiciary should be sanitized and corrupt members should be heavily sanctioned.